Rough country - Sandford, John, 1944 Feb. 23- (New York : G.P. Putnam's Sons, 2009)
While competing in a fishing tournament in a remote area of northern Minnesota, Minnesota Bureau of Criminal Apprehension investigator Virgil Flowers gets a call from Lucas Davenport to investigate a murder at a nearby resort, where a woman has been shot while kayaking.
Keywords: Police -- Minnesota -- Fiction; Murder -- Investigation -- Fiction; Stillwater (Minn.) -- Fiction; Suspense fiction; Mystery fiction